Autoantibodies as Diagnostic Markers and Mediator of Joint Inflammation in Arthritis - Qinghua Fang; Jiaxin Ou; Kutty Selva Nandakumar (Mediators of Inflammation)
Rheumatoid arthritis is a systemic, polygenic, and multifactorial syndrome characterized by erosive polyarthritis, damage to joint architecture, and presence of autoantibodies against several self-structures in the serum and synovial fluid. These autoantibodies (anticitrullinated protein/peptide antibodies (ACPAs), rheumatoid factors (RF), anticollagen type II antibodies, antiglucose-6 phosphate isomerase antibodies, anticarbamylated protein antibodies, and antiacetylated protein antibodies) have different characteristics, diagnostic/prognostic value, and pathological significance in RA patients. Some of these antibodies are present in the patients’ serum several years before the onset of clinical disease. Various genetic and environmental factors are associated with autoantibody production against different autoantigenic targets. Both the activating and inhibitory FcγRs and the activation of different complement cascades contribute to the downstream effector functions in the antibody-mediated disease pathology. Interplay between several molecules (cytokines, chemokines, proteases, and inflammatory mediators) culminates in causing damage to the articular cartilage and bones. In addition, autoantibodies are proven to be useful disease markers for RA, and different diagnostic tools are being developed for early diagnosis of the clinical disease. Recently, a direct link was proposed between the presence of autoantibodies and bone erosion as well as in the induction of pain. In this review, the diagnostic value of autoantibodies, their synthesis and function as a mediator of joint inflammation, and the significance of IgG-Fc glycosylation are discussed.